2022
DOI: 10.1186/s12880-022-00928-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the use of advanced magnetic resonance imaging in lupus nephritis

Abstract: Objectives To investigate the correlation between the histopathology of the kidney and clinical indicators in patients with lupus nephritis (LN) using magnetic resonance imaging (MRI). Methods A total 50 female participants were enrolled in the study. Thirty patients with LN were divided into types 2, 3, 4, and 5, according to their pathological features. The control group consisted of 20 healthy female volunteers. Serum creatinine, C3, C1q, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Shi et al 42 conducted a BOLD study on 23 LN and 18 healthy volunteer kidneys, and the mean renal R2* values were higher in LN patients than in healthy volunteers, with higher R2* values in class V patients than in class IV and class III patients. Similar findings were obtained by Chen et al, 9 who showed an increase in R2* values in LN patients compared to controls ( p < 0.05), but the most significant increase was found in the class IV group. In addition, the R2* values were positively correlated with SLE disease activity index score, total pathological score, activity index (AI), CI, renal tissue C3, and C1q ( p < 0.05).…”
Section: Research Progress Of Functional Magnetic Resonance Imaging I...supporting
confidence: 90%
See 4 more Smart Citations
“…Shi et al 42 conducted a BOLD study on 23 LN and 18 healthy volunteer kidneys, and the mean renal R2* values were higher in LN patients than in healthy volunteers, with higher R2* values in class V patients than in class IV and class III patients. Similar findings were obtained by Chen et al, 9 who showed an increase in R2* values in LN patients compared to controls ( p < 0.05), but the most significant increase was found in the class IV group. In addition, the R2* values were positively correlated with SLE disease activity index score, total pathological score, activity index (AI), CI, renal tissue C3, and C1q ( p < 0.05).…”
Section: Research Progress Of Functional Magnetic Resonance Imaging I...supporting
confidence: 90%
“…Their study also found statistically significant differences in mean cortical and medullary FA in stage 1 and 2 chronic kidney disease (CKD) compared to controls, which contributes to the early detection of LN cases. 5 Similar findings were obtained by Chen et al, 9 who showed that FA decreased in both cortical and medullary areas in the LN group compared to the control group, and the greatest decrease was observed in the class IV group. Hassan et al speculated that these changes in FA values may be related to changes in tubular injury, tubular flow, microcirculation, and interstitial fibrosis, which reduce the number of radially oriented structures and thus FA values, and are more reflected in the medulla.…”
Section: Diffusion Tensor Imagingsupporting
confidence: 79%
See 3 more Smart Citations